Collisional lipid exchange among DIBMA-encapsulated nanodiscs (DIBMALPs). (December 2018) - Danielczak, Bartholomäus; Keller, Sandro
Graphical abstract: Highlights: Lipid transfer among DIBMALPs is slower than among SMALPs but much faster than among LUVs or MSP nanodiscs. Lipid transfer among DIBMALPs is dominated by binary and ternary collisions at millimolar lipid concentrations. Lipid transfer among DIBMALPs becomes faster with ionic strength, that is, increasing salt concentration. Lipid transfer among DIBMALPs becomes faster with nanodisc size, that is, decreasing charge density. Abstract: Copolymers of diisobutylene/maleic acid (DIBMA), styrene/maleic acid (SMA), and styrene/maleimide (SMI) solubilise membrane proteins and surrounding lipids directly from artificial and biological membranes to form polymer-bounded nanodiscs. Although they preserve a lipid-bilayer core, these nanodiscs are much more dynamic than other membrane mimics, as we have recently demonstrated for two SMA variants. Here, we used time-resolved Förster resonance energy transfer spectroscopy to quantify the kinetics and unravel the mechanisms of lipid transfer among DIBMA-encapsulated nanodiscs (DIBMALPs), with particular emphasis on the role of Coulombic repulsion, which is modulated by ionic strength and nanodisc size. Our results show that DIBMALPs exchange lipids through both binary and ternary collisions on the timescale of seconds to minutes under typical experimental conditions. By contrast, nanodiscs bounded by SMA polymers exchange lipids considerably faster through binary collisions, whereas vesicles and nanodiscs based on membrane scaffold proteins exchange lipids much more slowly through lipid monomer diffusion. As DIBMALPs are polyanionic, collisional lipid transfer is substantially accelerated by screening of Coulombic repulsion caused by increasing ionic strength or nanodisc size. Analysis of the ionic-strength dependence in terms of an extended version of the Debye–Hückel equation suggests an effective DIBMALP charge number of z  = −47, which is considerably larger than that previously determined for nanodiscs bounded by more hydrophobic SMA polymers.